Holmes Rolston III: interview by Theo Horesh - Rolston, Holmes, 1932-2025, author; Horesh, Theo, author; Bäuu Press, publisher (Colorado State University. Libraries, 2015)
Rolston on how we might more wisely approach the "perfect moral storm" of climate change. Ethicists will watch the worldview, the interpretation, the value choices underlying economic analyses. We are at a hinge point in human and Earth history. We have enormous amounts of power but have not learned to control our appetites. How do we value the extinctions of species we are causing? How do we value diversity on our wonderland planet? What are the dangers of entering an Anthropocene Epoch? We can think of Earth as a promised land, a gift. Rolston has seen radical changes in human attitudes and behaviors in his lifetime. He challenges the millennial generation to press for more caring for Earth.

Theo Horesh interviewed Holmes Rolston III in 2013.
Keywords: climate change; ethics and economics; hinge point; species extinctions; Earth as gift; radical changes; Anthropocene Epoch